Coverage evaluation survey of COVID-19 vaccination among adolescents aged 12 to 17 years in the rural field practice area of medical college near Bangalore - Masthi, N. R. Ramesh; C. S., Niveditha (International Journal Of Community Medicine And Public Health, 2023)
Background: COVID-19 vaccination in India was started from 16 January 2021. The vaccination for adolescents was started one year later. The only source of COVID-19 vaccination coverage is government data. There is a lack of external studies on COVID-19 vaccine coverage in this age group. In this regard, the present study was taken up with the objectives to assess the vaccination coverage of COVID-19 among adolescents aged 12-17 years and the factors associated with COVID-19 vaccine hesitancy. Methods: A coverage evaluation survey was done for assessing COVID-19 vaccination coverage among adolescents aged 12 to 17 years from September to December 2022 in the rural field practice area of a medical college near Bangalore. Results: Out of the 420 study subjects, 294 (70%) were fully vaccinated, 70 (16.6%) were partially vaccinated and 56 (13.4%) were unvaccinated. It was observed that the coverage of COVID-19 vaccine in the age group of 15 to 17 years was higher compared to 12 to 14 years. Conclusions: The COVID 19 vaccine coverage with two doses among adolescents aged 12-14 was 61.9% and 78.1% among 210 adolescents aged 15 to 17 years in the rural locality. The most common reason for partial vaccination was that the school did not provide the second dose and the most common reason for not being vaccinated is that the subject was not eligible for vaccination during the school vaccination campaign.